Tendencias mundiales respecto al consumo de alimentos proteicos y las nuevas alternativas - Vigil Rodriguez, Hugo Alberto (2025)
This review provides an informative overview of the fundamental concepts of proteins and an overview of global trends in the current consumption of protein sources. It also presents possible future alternatives to mitigate the effects of global warming due to the high emission of greenhouse gases caused by the high consumption of animal-based foods. The intention is to promote a critical view regarding current eating habits and the new challenges that population growth will bring.